Dakwah Ekologi Berbasis Eco-Pesantren Pendekatan Dakwah Komunikasi Persuasif Tuan Guru Hasanain Juaini - putra pujiantara (Institut Agama Islam (IAI) Nurul Hakim, 2023)
Man as a creature of God swt created with reason and mind has an obligation to have ethics towards the environment . In the context of Islamic proselytizing, ecological proselytizing can be an alternative to preaching as a proselytizing medium that brings humans closer to the surrounding environment through a postulate approach sourced from the Qur'an and Hadits. One of the ecological proselytizing movements in writing is related to eco-islamic boarding school-based ecological proselytizing carried out by master teacher Hasanain Juaini at the Nurul Haramain Nahdlatul Wathan Narmada Islamic Boarding School, West Lombok. Tuan guru Hasanain Juaini is one of the religious leaders and leaders of islamic boarding schools who received many awards for his achievements in the field of ecological proselytizing. All forms of ecological activities of Tuan Guru Hasanain Juaini start from his potential to build a generation with an environmentally caring character in the person of his students at the Nurul Haramain Nahdlatul Wathan Narmada Islamic boarding school through the concept of Eco Pesantren to the point of contribution in the middle of society because the target of ecological proselytizing carried out by master teacher Hasanain Juaini is the community itself. This research focuses on the persuasive communication of master teacher Hasanain Juani in eco pesantren-based ecological da'wah at the boarding school Nurul Haramain Nahdlatul Wathan Narmada West Lombok, analyzed with communicative action theory and persuasive communication theory. The study uses qualitative research methods with phenomenological approaches as methods that lead to research to treat reality as a social construct. The results of this study show that the ecological proselytizing movement of tuan guru Hasanain Juaini made the community its target by using the concept of Eco Pesantren through environmental conservation movements such as greening, waste management and haramain integrated farming as a persuasive communication medium with the aim of persuasive proselytizing and dialogical proselytizing. The da'wah used is in the form of a method of balancing oral bil proselytizing, bil qalam, bil hal, and bil hikmah. The ecological proselytizing movement of master teacher Hasanain Juaini uses a persuasive communication model. Then it has an impact on changing awareness of the environment to the community so that green land increases, cleanliness of rivers and irrigation canals and can be of economic value to the Nurul Haramain Islamic Boarding School and the community.